(untitled) (Global Journal of Computer Science and Technology, 2024)
Artificial Intelligence Ethics is playing an important role with the development of Artificial Intelligence AI It is popular recognized that obeying to Artificial Intelligence Ethics guidelines and principles may resolve so many problems caused by Artificial Intelligence This paper reviewed the development history of Artificial Intelligence Ethics listed the main guidelines and principles of Artificial Intelligence Ethics proposed the methods of Artificial Intelligence Ethics governance discussed related algorithms to solve Artificial Intelligence Ethics problems